Autonomy in Relatedness: How Need Fulfillment Interacts in Close Relationships. (April 2020) - Kluwer, Esther S.; Karremans, Johan C.; Riedijk, Larisa; Knee, C. Raymond
A driving force of relationship maintenance is the fulfillment of basic psychological needs, in particular, the needs for relatedness and autonomy. Until now, research has considered the fulfillment of relatedness and autonomy needs as independent determinants of relationship functioning or as one merged construct called need fulfillment. Little is known about how motivational states interact, even though partners possess and pursue multiple needs at a time in everyday life. Combining theoretical insights from self-determination theory and family systems theory, we test the hypothesis that relatedness and autonomy need fulfillment interact to affect relationship maintenance behavior. In three studies ( N = 388, N = 241, and N = 220), we found that relatedness was positively related to accommodation, but especially (or only) when participants reported high, rather than low, autonomy. This research emphasizes the importance of maintaining a sense of self while being closely connected to the partner.